General Remarks on the Dwellings of the Pre-Historic Races in Orkney, with a Special Notice of the Picts' House of Skerrabrae, in the Parish of Sandwick, showing the Present State of the Excavations lately made there (Proceedings of the Society of Antiquaries of Scotland, 1867)
This article discusses brochs and barrows in Orkney with the aim of discovering more about the original inhabitants of Britain. The author speculates on how the age of these structures could be estimated by examining the architectural styles and any artefacts or human remains found during the excavations. The paper then focuses on William Watt’s excavations at Skara Brae, including some features of the structures and some of the finds unearthed on the site such as animal bones.